2014
DOI: 10.1099/mic.0.083501-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the Aggregatibacter actinomycetemcomitans ygiW–qseBC operon by QseB and integration host factor proteins

Abstract: The QseBC two-component system plays a pivotal role in regulating virulence and biofilm growth of the oral pathogen Aggregatibacter actinomycetemcomitans. We previously showed that QseBC autoregulates the ygiW-qseBC operon. In this study, we characterized the promoter that drives ygiW-qseBC expression. Using lacZ transcriptional fusion constructs and 59-rapid amplification of cDNA ends, we showed that ygiW-qseBC expression is driven by a promoter that initiates transcription 53 bases upstream of ygiW and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 59 publications
(65 reference statements)
0
16
0
Order By: Relevance
“…() showed that the PmrB sensor phosphorylates the non‐cognate QseB response regulator, which autoregulates the qseBC operon (see below). The pmrAB genes are not present in the A. actinomycetemcomitans genome but the QseB binding site in the ygiW‐qseBC promoter is identical to the consensus PmrA binding sequence in the pmrAB operon of E. coli (Juarez‐Rodriguez et al ., ). Hence, it is possible that in the absence of PmrAB, the A. actinomycetemcomitans QseC sensor may have evolved to integrate the iron and catecholamine sensory functions of the PmrAB and QseBC TCSs of E. coli .…”
Section: Activation Of the Qsec Sensormentioning
confidence: 97%
See 2 more Smart Citations
“…() showed that the PmrB sensor phosphorylates the non‐cognate QseB response regulator, which autoregulates the qseBC operon (see below). The pmrAB genes are not present in the A. actinomycetemcomitans genome but the QseB binding site in the ygiW‐qseBC promoter is identical to the consensus PmrA binding sequence in the pmrAB operon of E. coli (Juarez‐Rodriguez et al ., ). Hence, it is possible that in the absence of PmrAB, the A. actinomycetemcomitans QseC sensor may have evolved to integrate the iron and catecholamine sensory functions of the PmrAB and QseBC TCSs of E. coli .…”
Section: Activation Of the Qsec Sensormentioning
confidence: 97%
“…Similar to most other TCS, the activation of QseC leads to phosphorylation of the QseB response regulator and several studies have confirmed this either by directly demonstrating phosphate transfer (Clarke et al ., ) or by showing that site‐specific mutation of the conserved Asp 51 inhibits QseB function (Kostakioti et al ., ; Juarez‐Rodriguez et al ., ). In addition, using a mobility shift assay, Clarke & Sperandio (,b) demonstrated that phosphorylation of QseB is required for it to bind to QseB‐regulated promoters in vitro .…”
Section: Activation Of Qseb and Transcriptional Regulation Of Qsebcmentioning
confidence: 97%
See 1 more Smart Citation
“…CDM), and there is a basal level of activity under iron limiting conditions. In addition, our previous results and studies of QseBC in other species suggest that QseB may be activated by non-cognate sensor kinases [60,101]. This suggests that a minimal level of QseB activity is essential for A. actinomycetemcomitans and the absence of functional QseB triggers a stress response.…”
Section: Discussionmentioning
confidence: 80%
“…The histidine kinase sensor will then transfer the phosphate to the cognate response regulator causing it to change conformation and become activated. The activated response regulator can then bind to DNA to either promote or repress expression of certain genes, sometimes including its own operon [60,101]. There has also been evidence that some sensors can activate response regulators other than its own cognate response regulator [60].…”
Section: Two-component Regulatory Systems and Qsebcmentioning
confidence: 99%